1994
DOI: 10.1007/bf00865410
|View full text |Cite
|
Sign up to set email alerts
|

Statistical evidence consistent with two lactate turnpoints during ramp exercise

Abstract: A number of studies have identified the existence of two ventilation thresholds during ramp or incremental exercise to exhaustion on the cycle ergometer. This study was undertaken to investigate whether two threshold turnpoints could be identified in blood lactate concentration data collected at such times. Five trained athletes provided serial blood samples on several occasions each during a 3-month period of training. Blood lactate concentration was analysed by fitting models with no, one or two turnpoints. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The minimum duration necessary at each stage should be controlled for untrained and recreational athletes in further studies. Graduations with WL increment sizes of 40 or 50 W are sucient for lactate thresholds that are to be calculated using mathematical modelling and curve-®tting techniques (Hughson et al 1987;Berg et al 1990;Cheng et al 1992;Morton et al 1994). If QSS criteria are not accomplished in these protocols the underestimation of WL-related lactate values also has to be calculated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The minimum duration necessary at each stage should be controlled for untrained and recreational athletes in further studies. Graduations with WL increment sizes of 40 or 50 W are sucient for lactate thresholds that are to be calculated using mathematical modelling and curve-®tting techniques (Hughson et al 1987;Berg et al 1990;Cheng et al 1992;Morton et al 1994). If QSS criteria are not accomplished in these protocols the underestimation of WL-related lactate values also has to be calculated.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol is known to accomplish the criteria of QSS (Stockhausen et al 1994(Stockhausen et al , 1995. The AnT was estimated using the second turnpoint (LT2) in lactate concentration (Anuola and Rusko 1984;Ribeiro et al 1985;Morton et al 1994). …”
Section: Incremental Testmentioning
confidence: 99%
“…The rise of BL concentration during stepwise increase of workload is best described using a model with two turning points instead of continuous [10] or single breakpoint models [11]. A number of studies have identified the existence of two ventilatory thresholds or LTs during exercise to exhaustion.…”
Section: Energy Supply and Lactic Acid Production During Incremental Exercisementioning
confidence: 99%
“…In general, methods for determining the transition from aerobic to anaerobic metabolism are based on incremental exercise tests with exercise periods of 1-5 min (Beaver et al 1986;Cabbrera and Chizeck 1996;Cheng et al 1992;Davis et al 1983;Dickhuth et al 1999;Keul et al 1979;Kindermann et al 1979;Mader et al 1976;McLellan and Jacobs 1993;Morton et al 1994;Prusaczyk et al 1993;Ribeiro et al 1985;Stegmann et al 1981;Wasserman and McIlroy 1964;Wasserman and Whip 1975;Wasserman 1984). In addition, previous studies have pointed out that periods longer than 1-5 min are required to reach a steady state of LA (Foxdal et al 1996;Hughson et al 1987;Oyono-Enguelle et al 1990;Stegmann et al 1981;Uhrhausen et al 1993).…”
Section: Introductionmentioning
confidence: 98%